Research on SDN-based cloud security application - Jiang-yong SHI; Yue-xiang YANG; Wen-hua LI; Sen WANG (网络与信息安全学报)
SDN decoupled the control plane and data plane of traditional network,making the network programmable and simplifying the development of network applications.A comprehensive survey was made to current studies on SDN-based cloud security applications.Based on classification of the applications,the advantages and disadvantages of each application were studied and each category was summarized.What’s more,a service model of cloud security based on SDN was proposed,to overcome the inefficient of current works and integrate security with network service.Lastly,some suggestions about the future development of SDN-based cloud security applications were made.